(untitled) (Rudarsko-geološko-naftni zbornik, 2022)
The southeastern Hazara is a portion of the Himalayan Fold-Thrust Belt, formed by the interaction of the Indian Plate with the Eurasian Plate. The present research was conducted to analyse the structural geometry and assess the reservoir potential of the Cretaceous sequence (Chichali Formation and Kawagarh Formation) in southern Hazara, Pakistan. The mapped stratigraphic units range from Late Jurassic, Samana Suk Formation to early Eocene, Margalla Hill Limestone, along with unconformities. The research area is under intense deformation and is characterised by the thrust faults with accompanying folds. The fore-thrust faults are steeply dipping towards the north with associated back-thrust dipping southward, and the folds are mainly asymmetric anticlines and asymmetric synclines along with symmetric anticline (Barkot). The structures trend mainly NE-SW, indicating NW-SE compressive stresses. Reservoir quality is evaluated by using petrographic image analysis, SEM analysis, plug porosity, and permeability analysis. The porosity observed varies from 0.282% – 10.89%, 0.016% – 1.78% in Chichali (Sandstone) Formation and Kawagarh (Limestone) Formation, respectively. Simultaneously, the measured permeability in Chichali and Kawagarh Formation varies from 0–0.064 mD and 0–0.014 mD, respectively. The primary porosity type was intergranular/interparticle, intragranular, fracture, and vuggy porosity. SEM analysis shows that microporosity is present in the Cretaceous sequence and, calcite, dolomite, quartz, feldspar, and pyrite are the major minerals. The reservoir studies show that the Chichali Formation can be proven a good (Tight) reservoir rock, and Kawagarh Formation may prove as a reservoir (if the fractures in the subsurface, formed by severe tectonic deformation are not filled with cementing material) and seal/cap rock.